2011
DOI: 10.1002/art.30150
|View full text |Cite
|
Sign up to set email alerts
|

A distinct role for transient receptor potential ankyrin 1, in addition to transient receptor potential vanilloid 1, in tumor necrosis factor α-induced inflammatory hyperalgesia and Freund's complete adjuvant-induced monarthritis

Abstract: Objective. To investigate the involvement of transient receptor potential ankyrin 1 (TRPA1) in inflammatory hyperalgesia mediated by tumor necrosis factor ␣ (TNF␣) and joint inflammation.Methods. Mechanical hyperalgesia was assessed in CD1 mice, mice lacking functional TRP vanilloid 1 (TRPV1 ؊/؊ ) or TRPA1 (TRPA1 ؊/؊ ), or respective wildtype (WT) mice. An automated von Frey system was used, following unilateral intraplantar injection of TNF␣ or intraarticular injection of Freund's complete adjuvant (CFA). Kne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
147
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(158 citation statements)
references
References 47 publications
5
147
0
6
Order By: Relevance
“…In their studies, coinjection with 1 mM AP18 inhibited the acute nocifensive behavior induced by cinnamaldehyde during the first 5 min after injection (Petrus et al, 2007), and AP18 partially blocked the early phase of bradykinin-evoked mechanical hyperalgesia, which is thought to be mediated by activation of TRPA1 (Petrus et al, 2007;Wang et al, 2008). This indicates that AP18 has a short half-life in vivo; however, intraplantar injections of 1 mM AP18 that were given 24 h after complete Freund's adjuvant treatment were able to reverse complete Freund's adjuvant-induced mechanical hyperalgesia at 1 and 2 h postinjection (Petrus et al, 2007;Fernandes et al, 2010). In the present study, TRPA1 KO mice did not develop 4-ONE-induced mechanical hyperalgesia at 0.5 h postinjection although mechanical hyperalgesia was observed from 1 to 4 h postinjection in TRPA1 KO mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their studies, coinjection with 1 mM AP18 inhibited the acute nocifensive behavior induced by cinnamaldehyde during the first 5 min after injection (Petrus et al, 2007), and AP18 partially blocked the early phase of bradykinin-evoked mechanical hyperalgesia, which is thought to be mediated by activation of TRPA1 (Petrus et al, 2007;Wang et al, 2008). This indicates that AP18 has a short half-life in vivo; however, intraplantar injections of 1 mM AP18 that were given 24 h after complete Freund's adjuvant treatment were able to reverse complete Freund's adjuvant-induced mechanical hyperalgesia at 1 and 2 h postinjection (Petrus et al, 2007;Fernandes et al, 2010). In the present study, TRPA1 KO mice did not develop 4-ONE-induced mechanical hyperalgesia at 0.5 h postinjection although mechanical hyperalgesia was observed from 1 to 4 h postinjection in TRPA1 KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…A significant reduction in paw withdrawal thresholds (g) compared with baseline values was defined as mechanical hyperalgesia. In some experiments, 4-(4-chlorophenyl)-3-methyl-3-buten-2-one oxime (AP18) (25 nmol in 25 l of a 1 mM solution; Petrus et al, 2007;Fernandes, et al, 2010), a small-molecule TRPA1 receptor antagonist, was given intraplantarly 15 min before 4-ONE or vehicle injections. The injection pattern was always randomized, and all measurements were carried out by an observer blinded to treatment regimes and genotype of the mice.…”
mentioning
confidence: 99%
“…In addition to enhanced neurotransmitter release, stimulation of TRPV1 is associated with increases in inflammatory mediators contributing to joint inflammation (47). A recent study found that tumor necrosis factor-alpha (TNF-α)-induced mechanical hyperalgesia in an arthritic model could be blocked by a central, but not peripheral, injection of a TRPV1 antagonist (48). Similarly, interleukin-1 beta (IL-1β) can upregulate TRPV1 expression in arthritic rat DRG neurons, as well as sensitize articular C-fibers (48).…”
Section: Changes In Trp Stimulationmentioning
confidence: 99%
“…A recent study found that tumor necrosis factor-alpha (TNF-α)-induced mechanical hyperalgesia in an arthritic model could be blocked by a central, but not peripheral, injection of a TRPV1 antagonist (48). Similarly, interleukin-1 beta (IL-1β) can upregulate TRPV1 expression in arthritic rat DRG neurons, as well as sensitize articular C-fibers (48). Together, these findings indicate a novel link between TRP channels and cytokines in the generation of joint pain through central sensitization (44).…”
Section: Changes In Trp Stimulationmentioning
confidence: 99%
“…However, there are deficits in the response to mechanical stimuli [23,43]. Later it was found that like TRPV1 (see below), TRPA1 is actually involved in inflammatory-related hyperalgesia [44,45]. Most likely, this role is given by its activation or modulation by a great variety of chemical agents, including several inflammatory-or cell damage-related molecules.…”
Section: Trpa1mentioning
confidence: 99%